Enhancing the incorporation of Sn in vapor–liquid–solid GeSn nanowires by modulation of the droplet composition. (11th June 2022) - Zeghouane, Mohammed; Hijazi, Hadi; Bassani, Franck; Lefevre, Gauthier; Martinez, Eugenie; Luciani, Thierry; Gentile, Pascal; Dubrovskii, Vladimir G; Salem, Bassem
Abstract: We report on the influence of the liquid droplet composition on the Sn incorporation in GeSn nanowires (NWs) grown by the vapor−liquid−solid (VLS) mechanism with different catalysts. The variation of the NW growth rate and morphology with the growth temperature is investigated and 400 °C is identified as the best temperature to grow the longest untapered NWs with a growth rate of 520 nm min −1 . When GeSn NWs are grown with pure Au droplets, we observe a core–shell like structure with a low Sn concentration of less than 2% in the NW core regardless of the growth temperature. We then investigate the impact of adding different fractions of Ag, Al, Ga and Si to Au catalyst on the incorporation of Sn. A significant improvement of Sn incorporation up to 9% is obtained using 75:25 Au–Al catalyst, with a high degree of spatial homogeneity across the NW volume. Thermodynamic model based on the energy minimization at the solid–liquid interface is developed, showing a good correlation with the data. These results can be useful for obtaining technologically important GeSn material with a high Sn content and, more generally, for tuning the composition of VLS NWs in other material systems.